2007
DOI: 10.1111/j.1600-6143.2007.01972.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Depletional Induction and Posttransplant Lymphoproliferative Disease in Kidney Recipients Treated With Alemtuzumab

Abstract: Transplant patients are at the risk for posttransplant lymphoproliferative disease (PTLD), a virally-driven malignancy. Induction with the depleting antibody preparations Thymoglobulin and OKT3 is associated with PTLD suggesting that the T-cell depletion increases PTLD risk. We therefore studied 59560 kidney recipients from the Organ Procurement and Transplantation Network/United Network for Organ Sharing (OPTN/UNOS) database for a relationship between induction agent use and PTLD. Two agents with comparable T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
120
2
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(135 citation statements)
references
References 21 publications
9
120
2
4
Order By: Relevance
“…The highest risk was limited to EBV-seronegative recipients with the clinical implication that sirolimus should probably be avoided in this population, especially in those who are already at higher risk for PTLD. (Kirk et al, 2007) Nee et al also noted the same higher risk of PTLD with sirolimus, in a retrospective cohort of 53,719 kidney transplant recipients. (Nee et al, 2011) It seems that antimetabolites such as azathioprine and mycophenolate mofetil used primarily as adjunct therapy alongside calcineurin inhibitors for preventing allograft rejection, are associated with a lower or not increased risk of PTLD.…”
Section: Immunosuppressionmentioning
confidence: 79%
See 2 more Smart Citations
“…The highest risk was limited to EBV-seronegative recipients with the clinical implication that sirolimus should probably be avoided in this population, especially in those who are already at higher risk for PTLD. (Kirk et al, 2007) Nee et al also noted the same higher risk of PTLD with sirolimus, in a retrospective cohort of 53,719 kidney transplant recipients. (Nee et al, 2011) It seems that antimetabolites such as azathioprine and mycophenolate mofetil used primarily as adjunct therapy alongside calcineurin inhibitors for preventing allograft rejection, are associated with a lower or not increased risk of PTLD.…”
Section: Immunosuppressionmentioning
confidence: 79%
“…The use of antibody preparations that deplete T cells has been identified as a risk factor for PTLD in early studies by both univariate and multivariate analyses. ( Faull et al, 2005;Kirk et al, 2007;Opelz & Dohler, 2004;Yang et al, 2008) However, data from multiple transplant registries have demonstrated mixed results regarding a direct association between the use of Thymoglobulin and the risk of developing PTLD. (Marks et al, 2011) Quinlan et al in a retrospective cohort study among 156,740 kidney transplant recipients reported that the use of antibody induction or antirejection therapies was not associated with PTLD risk, even when restricted to T-cell-based therapies, in contrast to earlier reports where there was an association between antibody induction therapy and risk of early onset PTLD.…”
Section: Immunosuppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the studies that reported lower incidence of malignancies including PTLD in patients who had induction therapy with rabbit ATG may be blighted by inadequate sample size, non-standardization of doses maintenance immunosuppression and inadequate follow-up period [78][79][80][81][82][83][84][85].…”
Section: Malignancymentioning
confidence: 99%
“…1,2 Most occurrences of PTLD originate from uncontrolled Epstein-Barr virus (EBV) activation, which causes an unregulated transformation and proliferation of nodal and extranodal lymphocytes. 2 Within populations of transplant patients, the disorder usually has an incidence rate that ranges between 1% and 2%; however, it can have a higher incidence in pediatric populations.…”
Section: Introductionmentioning
confidence: 99%